Ice-colloidal templated carbon host for highly efficient, dendrite free Li metal anode - Patrike, Apurva; Kaniyamparambil, Karthika; Wahid, Malik; Chaturvedi, Vikash; Shelke, Manjusha (Carbon, 2021)
With its high theoretical specific capacity value, lithium metal itself would be an ideal anode material for rechargeable Li-ion batteries (LIBs). However, practical application of lithium metal is obstructed due to lithium dendrite growth during cycling leads to unstable SEI formation, volume fluctuation and safety hazard. Herein, we have developed a novel high surface area carbon network with both meso (∼20 nm) and micron (∼1–2 μm) size porosity, via ice-colloidal templating, as a scaffold for stable lithium metal anode mitigating lithium dendrite formation. The 3D porous nitrogen doped carbon (3D PNC) network is capable of lithium deposition equivalent to 10 mAhcm−2 at 2 mAcm−2 current density with 99.96% coulombic efficiency for 100 cycles. Moreover, 3D PNC when subjected to 3000 h of continuous plating-stripping measurements (∼700 cycles) depicts the coulombic efficiency of 99.84% with no observable dendrite growth at the current density of 2 mAcm−2 and lithium intake capacity of 5 mAhcm−2. A full cell of lithium plated 3D PNC anode with LiFePO4 shows an excellently stable performance up to 50 cycles at an input current density of 50 mAg−1, with a coulombic efficiency retention of 99.73%.